Clinical approach and diagnosing ulcerative colitis in a 55 years old man patient: a case report - Nurcahya, I. Gusti Ngurah Metta; Wirawan, M. S. (International Journal of Research in Medical Sciences, 2022)
This article reports a 55 years old man came to the emergency department with complaint fatigue and weakness since 6 day ago. Patient have 1 week history of diarrhoea with abdominal pain since 1 day ago. Patient also had nausea since 1 day ago. The patient does not take NSAID. Physical examination showed abdominal distention and pain on left iliac region. Colonoscopy showed many ulcus from rectum towards the descendent colon. The diagnosis of ulcerative collitis were made. The patient was treated with amino salisilate, antibiotics, steroids medications and showed clinical remission.